Challenges and Complexities in Teacher Conceptualization of Dynamic Assessment in the L2 Classroom: A Case Study in Türkiye - Meryem Özdemir-Yılmazer; Yonca Özkan (Profile: Issues in Teachers' Professional Development)
Dynamic assessment is a dialectic procedure requiring teachers to assess learners’ progress by paying attention to students’ errors while providing graduated prompts to help them fix them. Although previous studies have focused on the teachers’ competence in carrying out the dynamic assessment, this case study explores the dynamic assessment conceptualization of two English language teachers. Data were gathered through video-recorded sessions, reflective reports, semi-structured interviews, and classroom observations. Results showed that while one of the teachers reconceptualized her role as a graduated prompt provider, the other teacher resisted adopting any roles that dynamic assessment requires. The study implies careful consideration of personal and contextual factors shaping teachers’ assumptions to make a change in teacher practice.